The Effect Of Feeding Katuk Leaves And Moringa Leaves On Milk Production - Dinengsih, Sri; Kundaryanti, Rini; Nuhaniar, Rajenia (JKM (Jurnal Kebidanan Malahayati), 2025)
Latar Belakang : Pada tahun 2018 Indonesia data cakupan bayi yang mendapatkan ASI eksklusif sebesar 68,74%, di Provinsi Jawa Barat memiliki presentase cakupan ASI eksklusif sebesar 90,79% dengan persentase gizi buruk sebesar 2,5% dan gizi kurang sebesar 8,1% .Tujuan : Penelitian ini bertujuan untuk mengetahui  Pengaruh pemberian air rebusan daun katuk dan daun kelor  terhadap produksi ASI pada ibu nifas di wilayah kerja puskesmas parung Panjang tahun 2023.Metodologi : Desain penelitian ini dengan quasi experiment Two Group Pre-Post Test . P opulasi dalam penelitian ini adalah ibu nifas di wilayah kerja puskesmas Parung Panjang Bogor Jawa Barat Tahun 2023. Teknik pengambilan sampel menggunakan Purposive Sampling. Sampel berjumlah 30 orang, dikelompokkan menjadi 2 kelompok yaitu 15 orang diberikan intervensi rebuhan daun kelor dan 15 orang diberikan daun katuk. Analisa data Univariat dan Bivariat uji Paired T-test.Hasil Penelitian : Nilai rata-rata produksi ASI sebelum pemberian air rebusan daun katuk adalah 2.87 dan sesudah pemberian rebusan daun katuk adalah 3.93 (p value : 0.004) Nilai rata-rata produksi ASI sebelum pemberian air rebusan daun kelor adalah 2.80 dan sesudah pemberian rebusan daun kelor adalah 4.13. (p value : 0.004)Simpulan : Tidak ada Perbedaan rata rata produksi ASI yang signifikan pada kelompok sesudah diberikan air rebusan daun kelor dibandingkan pada kelompok sesudah diberikan air rebusan daun katuk ( p value : 0,430) (Uji Mean Whitney)Saran : Diharapkan pemanfaatan daun kelor dapat diolah menjadi sayuran sebagai menu selingan yang dapat dikonsumsi oleh ibu nifas selain olahan daun katuk. Kata kunci : ASI, Daun kelor, Katuk. ABSTRACT Background: In 2018 Indonesia data on the coverage of infants who get exclusive breastfeeding is 68.74%, in West Java Province has a percentage of exclusive breastfeeding coverage of 90.79% with a percentage of malnutrition of 2.5% and undernutrition of 8.1%.Objective: This study aims to determine the effect of giving boiled water of katuk leaves and moringa leaves on breast milk production in postpartum women in the working area of the Parung Panjang health centre in 2023.Methodology: This research design with quasi experiment Two Group Pre-Post Test. The population in this study werem postpartum mothers in the working area of the Parung Panjang Community Health Centre, Bogor, West Java in 2023. The sampling technique used purposive sampling. The sample amounted to 30 people, grouped into 2 groups, namely 15 people given the intervention of moringa leaf decoction and 15 people given katuk leaves. Univariate data analysis and Bivariate Paired T-test test.Results: The mean value of breast milk production before giving water decoction of katuk leaves was 2.87 and after giving water decoction of katuk leaves was 3.93 (p value: 0.004) The mean value of breast milk production before giving water decoction of moringa leaves was 2.80 and after giving water decoction of moringa leaves was 4.13. (p value: 0.004)Conclusion: There is no significant difference in average breast milk production in the group after being given moringa leaf decoction water compared to the group after being given katuk leaf decoction water (p value: 0.430) (Mean Whitney test).Suggestion: It is expected that the use of moringa leaves can be processed into vegetables as a side menu that can be consumed by postpartum mothers in addition to processed katuk leaves. Keywords: Breast milk, Moringa leaves, Katuk